Endogenous preferences: how credit affects households’ financial assets - Farinha, Rui Alexandre Creado da Silva (2015)
Endogenous preferences are a way of correcting one of the problems created by the concept of rationality used by Neoliberal economists. Preferences being endogenous mean that, among others, Institutions affect their outcome. One of the Institutions is the credit market. This dissertation analyses how credit market affects households ‘ financial assets in Portugal, since in a world of increasing financialization, correcting the failures of rationality in this area should be a priority. Since Keynes have been recognized reasons for holding money or not, and how to apply it, incorporated in liquidity preference, and which can be justified today at the light of behavioural economics. With the use of framing and isolation effects, mental accounting and loss aversion, households are expected to take into account the effects that credit has in their liquidity preference and rearrange their portfolio. Using an econometric model, the conclusions are in accordance with the theory, with households preferring assets of higher liquidity when they can't obtain consumption credit, so that they can obtain currency faster, and the use of consumption credit as an explanatory variable produces better results than models without it.